Variability of mesophyll conductance in grapevine cultivars under water stress conditions in relation to leaf anatomy and water use efficiency. (12th March 2014) - Tomás, M.; Medrano, H.; Brugnoli, E.; Escalona, J.M.; Martorell, S.; Pou, A.; Ribas‐Carbó, M.; Flexas, J.
Abstract Background and Aims Stomatal (gs) and mesophyll conductance (gm) limit photosynthesis significantly and consequently, apart from gs, gm is also a physiological process that could affect leaf water use efficiency (WUE). The aims of the present study were to analyse the genetic variability of gm in the grapevine, to relate the variability of leaf WUE with relative changes in gs and gm and to analyse the importance of leaf structural parameters in the variability of gm. Methods and Results The gm in seven potted grapevine cultivars (Vitis vinifera L.) were compared in three experiments under irrigation and moderate water stress treatments. Significant variability of gm was observed among cultivars associated with change in intrinsic WUE. No clear relationship with anatomical traits was found. Conclusions Variability of gm was associated with leaf WUE, although it could not be explained by anatomical variability. It is likely that biochemical mechanisms play an additional important role in the diffusion of CO2 in grapevines. Significance of the Study This study shows that the variability of gm in different grapevine cultivars offers a potential target for improving leaf WUE by increasing net photosynthesis (AN) without increasing plant water losses.